Reproductive factors and cardiometabolic disease among middle-aged and older women: a nationwide study from CHARLS - Wang, Qiong; Pang, Bo; Wu, Jing; Li, Chunyan; Niu, Wenquan (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiometabolic disease is skyrocketing to epidemic proportions due to the high prevalence of its components and the aging of the worldwide population. More efforts are needed to improve cardiometabolic health. The aim of this nationally representative study based on the China Health and Retirement Longitudinal Study (CHARLS, 2014–2018) was to examine the association between reproductive factors and cardiometabolic disease among Chinese women aged ≥45 years. Methods The CHARLS is an ongoing longitudinal study initiated in 2011, and the latest follow-up was completed in 2018. In total, 6,407 participants were analyzed. Effect-sizes are expressed as odds ratios (OR) and 95% confidence intervals (CI). Confounding was considered from statistical adjustment, subsidiary exploration, and unmeasured confounding assessment aspects. Results Of 6,407 accessible participants, 60.9% were recorded as having one or more of five predefined cardiovascular or metabolic disorders. Compared to those with two children, participants who had 0–1 child were found to have a lower risk of cardiometabolic disease (OR = 0.844, 95% CI: 0.714–0.998), and those who had ≥3 children had a greater risk (OR = 1.181, 95% CI: 1.027–1.357). Age at menarche of 16–18 years was a protective factor compared with ≤16 years of age (OR = 0.858, 95% CI: 0.749–0.982). In contrast, participants with a history of abortion were 1.212 times more likely to have cardiometabolic disorders (OR = 1.212, 95% CI: 1.006–1.465). The likelihood for the presence of unmeasured confounding was low, as reflected by E-values. Conclusions Our findings demonstrate that number of children, age at menarche, and history of abortion were associated with a significant risk of cardiometabolic disease among Chinese women aged ≥45 years.